THE EFFECTS OF CORRECTIVE FEEDBACK ON FLUENCY AND ACCURACY IN 4/3/2 ACTIVITY: A CASE OF STUDENTS AT ELTO SPELL-OUT PROGRAM - Muntasir, Muntasir; Fadhlur Rahman,; Muhammad Haekal, (Elite : English and Literature Journal, 2022)
ABSTRACT Due to limited time in the language classroom, teachers cannot set a huge number of goals for their students in teaching-learning process. The 4/3/2 activity, which is becoming increasingly popular among ESL teachers, is the focus of this research. The corrective feedback strategy is offered in this study as a way to improve the 4/3/2 activity. There were four participants in the study, all of whom were English Language Training for Officials (ELTO) spell-out students from Southeast Asian countries. They underwent a short course at Victoria University of Wellington, New Zealand. The findings suggest that fluency development is best served by 4/3/2 activity. Especially, respondents' fluency in both activities improved as a result of the time constraints. Surprisingly , there is not enough evidence to support the claim that both activities are more valuable in terms of accuracy's improvement. Despite the fact that corrective feedback has been incorporated into the activity, the results show no significant change. While adjusting the 4/3/2 activity can help, it does not take the place of adjusting the activity's priority. Correct feedback does not interfere with fluency improvement, hence this claim is disproved.